2015
DOI: 10.1021/acs.organomet.5b00205
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition and C–H Activation Reactions of a Tantalum Alkylidyne

Abstract: The alkylidyne complex (C5Me5)­Ta­(CPh)­(PMe3)2Cl (1) was first reported by Schrock in 1978, but little if any follow-up work on 1 or other group 5 metal alkylidynes has been reported. This work discloses two avenues of reactivity of 1. Treatment of 1 with 3-hexyne resulted in the formation of a tantalacyclobutadiene. Abstraction of chloride from 1 led to a mixture of products that included isomers of [(C5Me5)­Ta­(CHPh)­(CH2PMe2)­(PMe3)]+ (4), in which a C–H bond of a PMe3 ligand was added across the TaC bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 59 publications
0
18
0
10
Order By: Relevance
“…The high reactivity of L 4 M(CH 2 PMe 2 ) complexes (M = Co, Fe) and other phosphino methanide complexes 3,6,7,13,15,25,[31][32][33][34][35] prompted us to investigate the reactivity of the unprecedented complex 5. Most notable is the W(PMe 3 ) 3 (η 2 -CH 2 PMe 2 )H complex, which was reported as an electron-rich and highly reactive complex for the hydrodesulfurization of thiophenes.…”
Section: Reactivity Of Complexmentioning
confidence: 99%
“…The high reactivity of L 4 M(CH 2 PMe 2 ) complexes (M = Co, Fe) and other phosphino methanide complexes 3,6,7,13,15,25,[31][32][33][34][35] prompted us to investigate the reactivity of the unprecedented complex 5. Most notable is the W(PMe 3 ) 3 (η 2 -CH 2 PMe 2 )H complex, which was reported as an electron-rich and highly reactive complex for the hydrodesulfurization of thiophenes.…”
Section: Reactivity Of Complexmentioning
confidence: 99%
“…The reaction of the tantalumc arbynec omplex 76 with Me 3 SiCCSiMe 3 produced the tantalacyclobutadiene 77 (Scheme 17), [47] and reaction of the carbyne complex 78 with 3-hexyne gave either the tantalacyclobutadienes 79 or 80 depending on the reaction conditions. [48] Reactions of the rhenium carbyne complex 81 with internal acetylenes RCCR (R = Et, nPr, iBu)g ave fluxional rhenacyclobutadienes 82 (Scheme 18). An X-ray study of 82 a confirmed that the complex can be described as at rigonal-bipyramidal complex in which the equatorial positions are occupied by N, O, and Ca toms.…”
Section: Scheme14mentioning
confidence: 99%
“…Formal replacement of carbon atoms or CH groups in annulenes and dehydroannulenes by an isolobal transitionmetal fragment would give metallaannulenes and metalladehydroannulenes.W hile annulenes with the number of ring carbon atoms up to 30 and dehydroannulenes with the number of ring carbon atoms up to 38 are known, reported examples of metallaannulenes and metalladehydroannulenes are mainly those with six or less ring atoms,f or example, metallacyclobutadienes (3), [2,3] metallabenzenes (4), [4,5] dimetallabenzenes (5), [6] and metallabenzynes (6). [7,8] Larger metallaannulenes and metalladehydroannulenes are very rare.V ery recently,X ia nd his co-workers reported the synthesis and characterization of the first dimetalla- [10]annulenes (7).…”
mentioning
confidence: 99%